Odpowiedzi

Najlepsza Odpowiedź!
2010-04-08T13:35:53+02:00
4x-54=x+54
4x-x=54+54
3x=108 /:3
x=36

4x=20 /:4
x=5

1+2x+5*(41-1-x)=150
1+2x+5*(40-x)=150
1+2x+200-5x=150
2x-5x=150-1-200
-3x=-51 /:(-3)
x=17

2x+100=110
2x=110-100
2x=10 /:2
x=5

4x+1=3x+5
4x-3x=5-1
x=18

4*(4-1)=6*(x+1)
4x-4=6+6x
4x-6x=4+6
-2x=10 /:(-2)
x= -5

11-y=y+2y-5
11-y=3y-5
-y-3y=-11-5
-4y=-16 /:(-4)
y=4

5x+2=7-3x
5x+3=-2+7
8x=5 /:8
x=5/8

3(x-1)=0
3x-3=0
3x=0+3
3x=3 /:3
x=1

-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x=-5

Mam nadzieję, że pomogłam :)
mam pytanie czy w tym jednym x